Optimization of Hexadentate Bispidine Ligands as Chelators for 64CuII PET Imaging - Comba, Peter; Starke, Miriam; Wadepohl, Hubert (ChemPlusChem, 2018)
The coordination chemistry of the hexadentate bispidine ligand L1 with three pyridine, one pyridazine, and two tertiary amine donors with CuII and ZnII is reported. The substitution of one of the two cis-disposed pyridine donors in-plane with the two tertiary amines of the bispidine backbone by a pyridazine group was predicted to substantially reduce distortion from planarity of the tetradentate subunit and therefore was assumed to lead to higher CuII complex stability. The X-ray single-crystal structures of the ZnII and CuII complexes, which are in excellent agreement with the DFT- and MM-optimized structures, confirmed this prediction but indicated that deviation from planarity is appreciable. This also emerges from solution spectroscopy (UV/Vis/NIR and EPR of the CuII complex), which indicated that the in-plane ligand field is only slightly increased. The geometric parameters together with the lower basicity of pyridazine versus pyridine (pKa=2.33 vs. 5.23) are also in agreement with an only slightly more negative redox potential of the CuII/I couple (Eo=−780 vs. −760 mV, MeCN, vs. Fc/Fc+), and the potentiometrically determined CuII stability constant with L1 is slightly lower than that with the parent ligand L2 (log K=12.7 vs. 14.5). Therefore, modification of the donor groups is a more promising approach to increasing the stabilities of these complexes and yields 64CuII chelators that outperform known hexadentate bispidine ligands.
Gesehen am 03.06.2019